ASESSING STUDENTS’ CRITICAL READING UNDERSTANDING OF ENGLISH EDUCATION STUDY PROGRAM AT COKROAMINOTO UNIVERSITY OF PALOPO - Rahmawati Upa; Reski Yusrini Islamiyah Yunus; Sri Damayanti (Jurnal Vokatif: Pendidikan Bahasa, Kebahasaan, dan Sastra, 2024)
This research aims at examining critical reading understanding of the English Education Study Program students at Cokroaminoto Palopo University, this research is qualitative research and the type of research is descriptive research. The population in this research was the fourth semester students which consist of 44 students, and the sample is 10 students were taken using purposive sampling technique. The data of this research was collected through critical reading test and then the data were analyzed and categorized based on the rubric developed by Brown (2018). Based on the results of research and data analysis, it was concluded that generally the students already use critical reading, although there are several categories in critical reading which cannot be fully understood, the students already understand what is critical reading and how to use it in English reading texts. Dealing with the understanding, four of the students are categorized into mastering category, four are categorized into developing and only two of them is categorized into emerging.